Sistem Pendukung Keputusan Perankingan Sekolah Menengah Pertama Menggunakan Metode Fuzzy AHP dan TOPSIS - Mahayanti, Ni Wayan Surya; Waas, Devi Valentino (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
Determining the best school is a difficult choice for parents, besides the cost and distance from students' homes, there are other supporting factors that must be considered, namely the National Education Standards (SNP). In the implementation of the program to determine the best school based on the National Education Standards (SNP), the manual is now so the calculation process is complicated. Parents of students who have a lot of business are required to provide the best education for their children, so it is necessary to create a system to choose the best school for students. The decision support system created using the AHP model. The weighting method in AHP is used to determine the criteria weights according to the decision makers. The AHP method is then used to rank the best alternative from a number of alternatives. Determination of the best alternative ranking in this system refers to the National Education Standards (SNP), costs, distance from home and school achievement. as a criterion that will be assessed by a decision maker consisting of parents of students. The test results show that the system can rank the school correctly according to the manual calculation but the results show differences with the results from the Tabanan district education office. this is due to the assessment of the Office of Education not considering the importance of inter-criteria weight.